Phased Electromagnetic Acoustic Transducer Array for Rayleigh Wave Surface Defect Detection - Xiang, Lunci (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2020)
A phased electromagnetic acoustic transducer (EMAT) array system has been developed for the detection and characterization of surface-breaking defects. An array of four linear coils that are individually controlled is used to generate a Rayleigh wave. The high-current electronics combined with the coil designs enables the array to generate either narrowband or broadband signals, and controlling the phase delay between the channels makes it possible to change the ultrasound wavelength without requiring the physical separation of the coils to be changed. The experimental results show that the four-coil phased array can generate a wavelength range from 3.0 to 11.7 mm. Surface-breaking defects were characterized using a transmit-receive setup with a broadband EMAT detector being used to detect the Rayleigh wave. Machined surface slots with different depths were used for technique validation. The results show that the array is sensitive to surface defects and a wide depth sensitivity range for defect sizing can be easily achieved by applying phasing to tune the wavelength of operation. A large increase in detection flexibility is immediately shown